CD55 expression patterns on intestinal neuronal tissue are divergent from the brain. Issue 4 (11th March 2004) - Gelderman, K A; Zijlmans, H J M A A; Vonk, M J; Gorter, A
Abstract : Background and objectives: In this study, we investigated how enteric plexuses protect themselves from complement mediated attack. For this purpose, the expression patterns of membrane bound complement regulatory proteins (mCRP) and their association with C3 deposition was determined. In addition, mCRP expression patterns of enteric plexuses were compared with those in the central nervous system (CNS). Methods: Immunohistochemical stainings were performed to discriminate neuronal cells from glial cells and to detect the presence of CD46, CD55, CD59, and C3d. RNA in situ hybridisation (RISH) was used to determine the cell types that produce CD55 mRNA. Results: Enteric plexuses minimally expressed CD46 whereas CD55 and CD59 were highly expressed. CD55 expression was also observed in a ring around Auerbach's plexuses which was not observed for CD46 and CD59. C3d was deposited around the plexuses but plexus cells themselves did not stain for C3d. In contrast with CNS neurones, enteric neurones were shown to express CD55 whereas enteric glial cells did not. This was confirmed with CD55 RISH. Phospholipase C mediated cleavage of CD55 demonstrated that CD55 was most likely attached to elastic fibres surrounding the plexus. Attached CD55 might protect CD55 negative glial cells from complement mediated injury during inflammatory reactions. CD55 on elastic fibres surrounding the plexuses most likely originated from enteric neuronal cells. Conclusion: In contrast with the CNS, enteric neurones express CD55 and enteric glial cells lack CD55 expression. CD55, produced by neuronal cells, attached to elastic fibres surrounding the plexuses is proposed to protect the CD55 negative glial cells within plexuses.